2023
DOI: 10.3389/fcimb.2023.1107351
|View full text |Cite
|
Sign up to set email alerts
|

A multi-subgroup predictive model based on clinical parameters and laboratory biomarkers to predict in-hospital outcomes of plasma exchange-centered artificial liver treatment in patients with hepatitis B virus-related acute-on-chronic liver failure

Abstract: BackgroundPostoperative risk stratification is challenging in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) who undergo artificial liver treatment. This study characterizes patients’ clinical parameters and laboratory biomarkers with different in-hospital outcomes. The purpose was to establish a multi-subgroup combined predictive model and analyze its predictive capability.MethodsWe enrolled HBV-ACLF patients who received plasma exchange (PE)-centered artificial liver suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Among these factors, age is closely related to the severity of liver disease and poor prognosis 24 . Other studies have reported that age, PT, total bilirubin, infection, and hepatic encephalopathy are also independent factors for the prognosis of ACLF 25 , 26 . The DSM-ACLF (day-3) score includes the factors of blood glucose, triglycerides, very low-density lipoprotein and fibrin.…”
Section: Discussionmentioning
confidence: 92%
“…Among these factors, age is closely related to the severity of liver disease and poor prognosis 24 . Other studies have reported that age, PT, total bilirubin, infection, and hepatic encephalopathy are also independent factors for the prognosis of ACLF 25 , 26 . The DSM-ACLF (day-3) score includes the factors of blood glucose, triglycerides, very low-density lipoprotein and fibrin.…”
Section: Discussionmentioning
confidence: 92%